2016
DOI: 10.3390/rs8010050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Image-Based Point Cloud Products to Generate a Bare Earth Surface and Estimate Canopy Heights in a Woodland Ecosystem

Abstract: Abstract:We examine the utility of Structure from Motion (SfM) point cloud products to generate a digital terrain model (DTM) and estimate canopy heights in a woodland ecosystem in the Texas Hill Country, USA. Very high spatial resolution images were acquired with a Canon PowerShot A800 digital camera mounted on an unmanned aerial system. Image mosaicking and dense point matching were accomplished using Agisoft PhotoScan. The resulting point cloud was classified according to ground/non-ground classes and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 31 publications
5
77
1
1
Order By: Relevance
“…This well-known limitation of digital photogrammetry known as dead ground [29] is caused by the canopy obscuring the ground, resulting in significant omissions. Consistent with previous studies [39,40,46], our results revealed that the UAV-SfM technique is capable of capturing terrain over certain vegetated surfaces, such as sparse forests with large open areas, but does not function very well in forested areas with dense or closed canopies. This finding highlights the need for an accurate DTM from an alternative source to calculate canopy height with photogrammetric surface models in dense forest areas.…”
Section: Characterisation Of Forest Canopy Using the Uav-sfm Techniquesupporting
confidence: 80%
See 1 more Smart Citation
“…This well-known limitation of digital photogrammetry known as dead ground [29] is caused by the canopy obscuring the ground, resulting in significant omissions. Consistent with previous studies [39,40,46], our results revealed that the UAV-SfM technique is capable of capturing terrain over certain vegetated surfaces, such as sparse forests with large open areas, but does not function very well in forested areas with dense or closed canopies. This finding highlights the need for an accurate DTM from an alternative source to calculate canopy height with photogrammetric surface models in dense forest areas.…”
Section: Characterisation Of Forest Canopy Using the Uav-sfm Techniquesupporting
confidence: 80%
“…However, Jensen and Mathews [46] (RMSE = 1.24 m for Oak-Ash Juniper Savanah and closed canopy woodland using Hawkeye II UAV imagery) reported lower RMSE values for dominant height than ours. Puliti et al [38] also reported lower RMSE values for dominant height (RMSE = 0.72 m and relative RMSE = 3.5%), and basal area (RMSE = 4.49 m 2 /ha, relative RMSE = 15.4%).…”
Section: Estimation and Plot-level Validation Of Forest Structural Atcontrasting
confidence: 43%
“…Instead, the minimum elevation value point within each pixel was used to provide the best approximation of the terrain surface within vegetated areas, acknowledging that this can sometimes result in the extraction of false elevation values as a result of point scatter below the ground surface [29]. Vegetation filtering from the SfM-MVS datasets was not the focus of this study, but is an active area of research, e.g., [111][112][113]. If suitable vegetation filtering methods can be developed and easily applied to SfM-MVS datasets, it will greatly enhance the ability of SfM-MVS to accurately reconstruct ground topography in densely vegetated areas.…”
Section: Vegetationmentioning
confidence: 99%
“…Vegetation filtering is still a significant challenge at this very fine scale and reduces our ability to automate DTM difference processing. Our approach was to use the topographic position of points in the cloud to identify ground points, however, other SfM studies have used a variety of methods to filter vegetation with no clear consensus on a superior workflow [27,51,52,67,77]. In our semi-arid shrubland study area, there is a distinct difference in color between the creosote/mesquite shrubs and the bare ground.…”
Section: Dtm Errorsmentioning
confidence: 99%